2020
DOI: 10.1007/s00701-020-04254-4
|View full text |Cite|
|
Sign up to set email alerts
|

Integrity of dural closure after autologous platelet rich fibrin augmentation: an in vitro study

Abstract: Background Watertight closure of the dura mater is fundamental in neurosurgery. Besides the classical suturing techniques, a variety of biomaterials have been proposed as sealants. Platelet rich fibrin (PRF) is an autologous biomaterial which can readily be obtained through low-speed centrifugation of patient’s own blood. It is rich in fibrin, growth factors, leucocytes and cytokines and has shown adhesive properties while promoting the physiological wound healing process. In this study, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The secondary leak pressure was measured following the introduction of PRP augmentation. The PRP augmentation consistently strengthened the closure, with a four times higher leak pressure compared to standard running suture technique 21 .…”
Section: Outcomes Animal Studiesmentioning
confidence: 90%
See 1 more Smart Citation
“…The secondary leak pressure was measured following the introduction of PRP augmentation. The PRP augmentation consistently strengthened the closure, with a four times higher leak pressure compared to standard running suture technique 21 .…”
Section: Outcomes Animal Studiesmentioning
confidence: 90%
“…Other than the uid PRP, there is a solid one as well which comprises a 3d-matrix and is manually compressed and attened to form a membrane. The membrane, once formed, can be used for up to three hours 21,24,27 .…”
Section: Preparation Of Prpmentioning
confidence: 99%
“…As CSF leakage is an important complication of cranial surgery, this study is of major importance to the field of neurosurgery. Some preliminary pilot studies reported the feasibility of L-PRF as a closure aid in neurosurgery [ 9 , 16 ]. L-PRF has been reported to enhance wound healing by providing growth factors to the surrounding tissue [ 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…As CSF leakage is an important complication of EETA, this study is of major importance to the field of neurosurgery, skull base surgery, and ENT surgery. Some preliminary pilot studies reported the feasibility of L-PRF as a closure aid in neurosurgery [ 8 – 10 , 16 ]. In order to explore further possibilities of the use of L-PRF in cranial surgery, we are currently performing a similar randomized controlled trial in which L-PRF is compared to commercially available fibrin sealants for dural closure in supra- and infratentorial surgeries [ 17 ].…”
Section: Discussionmentioning
confidence: 99%